If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -45 + 15(x) = 0 Solving -45 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 15x = 0 + 45 Combine like terms: -45 + 45 = 0 0 + 15x = 0 + 45 15x = 0 + 45 Combine like terms: 0 + 45 = 45 15x = 45 Divide each side by '15'. x = 3 Simplifying x = 3
| -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x | | -2v-6v=-16 | | 0=4e+4 | | 36-3x=312-x | | 7t+1=162 | | 2x-3+21=-3 | | -45+15(15)=x | | y=2000+2500x-25000+2000x | | 2-(x-3)+6=8 | | 5n+9=54 | | -45+15(1)=x | | a-7a+3=6a+3 | | 1+3n+6=-5 | | (3+3i)+(2+4i)= | | -7w(w-2)=5(3-w) | | 2a^2+5a+18=0 | | 4(u+1)=20 | | x+5-5x=13 | | 5x-23=5x-1 | | 2x^3+5x^2-x-6=0 | | -8x+2=-6 | | 3=x+5-4 | | y+-6x+-9=0 | | (3x^3-24)=0 | | 4(3+5w)=11 | | ln(x^2+3x+4)=0 | | -15+2(x)=-11 | | -15+2(5)= |